The academic literacy mind map as acooperative learning strategy to develop efl basic writing skills amongst ninth-grade students at Bernardo Valdivieso high school, 2014 – 2015 academic period - Lima Salinas, Gabriela Estefania (2016)
This action research work focused on the use of academic literacy mind map as cooperative learning strategy to develop writing skills amongst ninth grade students at “Bernardo Valdivieso” high school. An intervention plan of eight weeks was carried out in this process to improve the skill. Tests and questionnaires were used to measure the students’ progress and perception of the usage of academic literacy mind map as a cooperative learning strategy. The scientific, descriptive, analytic-synthetic and statistic methods were used to analyze, describe the results and then, give conclusions and recommendations. The results obtained from the post test and questionnaire indicated that the use of this strategy facilitated meaningfully the improvement of the writing skill in the students; also it confirmed the enthusiasm and the positive attitude of the students toward working with the cooperative learning. Finally, the intervention done improved meaningfully the students’ grades